Fourier transforms of Dini-Lipschitz functions on Vilenkin groups - M. S. Younis (International Journal of Mathematics and Mathematical Sciences)
In [4] we proved some theorems on the Fourier Transforms of functions satisfying conditions related to the Dini-Lipschitz conditions on the n-dimensional Euclidean space Rn and the torus group Tn. In this paper we extend those theorems for functions with Fourier series on Vilenkin groups.